2017
DOI: 10.1155/2017/8916570
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Administration in Patients with Chronic Obstructive Pulmonary Disease: State of the Science

Abstract: Patients with chronic obstructive pulmonary disease (COPD) have chronic, irreversible airway inflammation; currently, there is no effective or curative treatment and the main goals of COPD management are to mitigate symptoms and improve patients' quality of life. Stem cell based therapy offers a promising therapeutic approach that has shown potential in diverse degenerative lung diseases. Preclinical studies have demonstrated encouraging outcomes of mesenchymal stem/stromal cells (MSCs) therapy for lung disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
0
24
0
6
Order By: Relevance
“…This new treatment modality for COPD patients is currently tested on clinical trials, varying in distinct stages of COPD, route of injection, type and dosage of cells, and outcomes [45]. MSCs show profound suppressive effects on immune cells and pathways, recent studies have indicated that MSCs suppress lung injury and inflammation in mouse models of inflammatory and immune mediated lung diseases [46].…”
Section: Interventions For Emphysema: Effectiveness and Safetymentioning
confidence: 99%
“…This new treatment modality for COPD patients is currently tested on clinical trials, varying in distinct stages of COPD, route of injection, type and dosage of cells, and outcomes [45]. MSCs show profound suppressive effects on immune cells and pathways, recent studies have indicated that MSCs suppress lung injury and inflammation in mouse models of inflammatory and immune mediated lung diseases [46].…”
Section: Interventions For Emphysema: Effectiveness and Safetymentioning
confidence: 99%
“…It is hypothesized that mesenchymal cells may provide antiinflammatory benefits or regenerative capability to more frequent conditions such as pulmonary fibrosis, chronic obstructive pulmonary disease, and pulmonary arterial hypertension. [16][17][18] Understanding the role of mesenchymal cells in PIG may also have implications for these other diseases. Conversely, PIG may benefit from some of the advances in these other diseases but in vitro and in vivo models are required to safely test new therapies before introducing these therapies to infants.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that mesenchymal cells may provide anti‐inflammatory benefits or regenerative capability to more frequent conditions such as pulmonary fibrosis, chronic obstructive pulmonary disease, and pulmonary arterial hypertension . Understanding the role of mesenchymal cells in PIG may also have implications for these other diseases.…”
mentioning
confidence: 99%
“…В связи с этим, активно ведётся разработка новых методов лечения ХОБЛ, основанных на применении таргетных лекарственных молекул и клеточной терапии, в частности, мезенхимальных стволовых клеток (МСК). Эксперименты по применению МСК для лечения хронических заболеваний бронхолёгочной системы показывают перспективность терапевтического использования МСК в терапии ХОБЛ [12,41,46,52]. МСК -плюрипотентные стволовые клетки, содержа-щиеся, главным образом, в костном мозге, способные к дифференцировке в различные ткани.…”
unclassified